Method for producing mixed conducting argyrodite-type solid electrolyte, argyrodite-type solid electrolyte produced thereby, active material-solid electrolyte composite powder and all-solid-state battery comprising the same
Patent Information
- Application Number
- KR1020220005626
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2022-01-14
- Publication Date
- 2026-09-18
- Estimated Expiration
- 2042-01-14
Smart Images

Figure 112022004973191-PAT00001_ABST
Abstract
Description
Technology Field
[0001] The present invention relates to a method for manufacturing a mixed-conductivity azirodite-based solid electrolyte, an azirodite-based solid electrolyte manufactured thereby, and an all-solid-state battery comprising the same. Background Technology
[0002] Rechargeable batteries refer to batteries that convert electrical energy into chemical energy for storage and then convert it back into electrical energy for use when needed; they are being actively researched as power sources for portable electronic devices, including laptops and mobile phones, as well as electric vehicles.
[0003] However, currently commercialized lithium-ion batteries utilize non-aqueous organic electrolytes, which present disadvantages such as flammability, corrosiveness, high volatility, and thermal instability. To address these drawbacks, research is underway to replace liquid electrolytes with solid electrolytes, and among various solid electrolyte structures, active research is being conducted on the azirodite structure.
[0004] In 'Lithium argyrodite(US 8075865 B2)', Li + (12-n-x) B n+ X 2- 6-x Y - x (B n+ is selected from the group consisting of P, As, Ge, Ga, Sb, Si, Sn, Al, In, Ti, V, Nb, and Ta, and X 2- is selected from the group consisting of S, Se, and Te, and Y - Lithium azirodite having the compositional formula selected from the group consisting of Cl, Br, I, F, CN, OCN, SCN and N3, satisfying 0 ≤ x ≤ 2 is presented.
[0005] 'Sulfide-based solid electrolyte for lithium ion batteries (US 9899701 B2)' presents Li6PS5Cl, a lithium ion conductive material with an azirodite-type crystal structure, and the crystal phase of Li6PS5Cl is composed of lithium (Li), phosphorus (P), sulfur (S), and chlorine (Cl), and is known to be stable as it is formed at relatively high temperatures.
[0006] If we look at 'Sulphide-based solid electrolyte for lithium-ion batteries (JP 5957144 B2)', Li 7-x PS 6-x Ha x Having the compositional formula (Ha is Cl or Br), with low sulfur deficiency, L * a * b * Value according to the color system (L * It proposes a sulfide-based solid electrolyte with a ) value of 60 or higher. To this end, Li 7-x PS 6-x Ha x In the case where Ha is Cl, the process includes adjusting x to 0.2 to 1.2, then mixing lithium sulfide (Li2S) powder, phosphorus sulfide (P2S5) powder and lithium chloride (LiCl) powder or lithium bromide (LiBr) powder by ball milling, and calcining at 350 to 500°C under an inert atmosphere or calcining at 350 to 650°C under an atmosphere containing hydrogen sulfide gas.
[0007] Meanwhile, conventional azirodite-based solid electrolytes, such as the aforementioned solid electrolyte, require high ionic conductivity and very low electronic conductivity between the anode and cathode. However, it is expected that the properties of the active material can be improved by enabling the solid electrolyte mixed into the anode or cathode plate to possess mixed conductivity characteristics, which are simultaneously high in both ionic and electronic conductivity; yet, according to conventional methods, it is difficult to manufacture a solid electrolyte with simultaneously high ionic and electronic conductivity.
[0008] Accordingly, there is an urgent need for the technological development of mixed-conductivity azirodite-based solid electrolytes that enable the control of charge and discharge characteristics of all-solid-state batteries through the control of ionic and electronic conductivity. Prior art literature
[0009] (Patent Document 0001) US 8075865 B2 (Patent Document 0002) US 9899701 B2 (Patent Document 0003) JP 5957144 B2 The problem to be solved
[0010] The present invention was developed to resolve the above-mentioned problems, and the technical problem is to provide a method for manufacturing a mixed-conducting azirodite-based solid electrolyte capable of controlling ionic conductivity of 0.1 mS / cm or more and electronic conductivity of 0.01 mS / cm or more, an azirodite-based solid electrolyte manufactured thereby, an active material-solid electrolyte composite powder containing the same, and an all-solid-state battery. means of solving the problem
[0011] To solve the above technical problem, the present invention comprises the steps of: reacting an azirodite-based solid electrolyte raw material comprising a lithium metal-containing material, a transfer catalyst that ionizes the lithium metal to transfer ions and electrons, a chalcogen element, and a compound of one or more elements selected from groups 2 to 15 and 17 of the periodic table in a polar aprotic solvent to produce a lithium metal polychalcogenide through which ions and electrons are transferred from the lithium metal-containing material to the chalcogen element, thereby preparing a precursor solution in which an azirodite-based solid electrolyte precursor exists in a state of suspension, dissolution, or a combination thereof; and recovering the azirodite-based solid electrolyte precursor in powder form from the precursor solution. The present invention provides a method for manufacturing a mixed-conductivity azirodite-based solid electrolyte, comprising the step of heat-treating the powder-form solid electrolyte precursor to produce an azirodite-based solid electrolyte; wherein the azirodite-based solid electrolyte is characterized in that its electronic conductivity and ionic conductivity are controlled according to the degree to which the polar aprotic solvent is carbonized by the heat treatment.
[0012] In the present invention, the azirodite-based solid electrolyte is characterized by being controlled to have an electron conductivity of 0.01 to 10,000 mS / cm and an ionic conductivity of 0.1 to 100 mS / cm.
[0013] In the present invention, the azirodite-based solid electrolyte is represented by the following chemical formula 1 and is characterized by containing 50 to 100 wt% of an azirodite crystal structure of space group F-43m.
[0014] [Chemical Formula 1]
[0015] (A + ) a (B n+ ) b (X 2- ) x (Y - ) y
[0016] In the above chemical formula 1, A = Li, B = P, X = S, Y = F, Cl, Br, I, and one or more halogen elements, and a + n * b - 2 * x - y = 0, a > 0, x > 0, and at least one of b and y is > 0, while a = 7-y, b = 1, x = 6-y, and 0.1 ≤ y ≤ 2.
[0017] In the present invention, the precursor solution is characterized in that the lithium metal-transfer catalyst radical generated by the reaction between the lithium metal-containing material and the transfer catalyst transfers lithium metal ions and electrons to the chalcogen element to form the lithium metal polychalcogenide, thereby dissolving and dispersing within the solution, and the polychalcogenide reacts or mixes with the B element, the Y element, or a compound thereof, so that the solid electrolyte precursor is prepared in a suspended, dissolved, or combined state in the solution.
[0018] In the present invention, the heat treatment step is characterized by crystallizing the powder-form solid electrolyte precursor at 400 to 600°C in an atmosphere of one or more of vacuum, inert gas, and hydrogen sulfide (H2S) gas.
[0019] In the present invention, the lithium metal-containing material is characterized by being selected from the group consisting of lithium metal, a lithium metal-transfer catalyst radical solution formed by reacting the lithium metal with the transfer catalyst in the polar aprotic solvent, and a mixture thereof.
[0020] In the present invention, the step of recovering the solid electrolyte precursor in powder form is characterized in that the precursor existing in a suspended state in the solution is separated and recovered by one or more methods of filtering, centrifugation, natural sedimentation, spraying, and hydrocyclone, and the precursor existing in a dissolved state or a combined state of suspension and dissolution in the solution is separated and recovered by one or more methods of heat drying, solvent exchange, and spray drying.
[0021] In the present invention, the transfer catalyst comprises naphthalene, acenaphthylene, acenaphthene, diphenyl, fluorene, phenanthrene, anthracene, fluoranthene, pyrene, benzo(a)anthracene, chrysene, benzo(k)fluoranthene, benzo(b)fluoranthene, benzo(a)pyrene, indeno(1,2,3-cd)pyrene, dibenz(a,h)anthracene, and It is characterized by being one or more polycyclic aromatic hydrocarbons (PAHs) selected from the group consisting of benzo(g,h,i)perylene.
[0022] In the present invention, the polar aprotic solvent is characterized by being one or more selected from the group consisting of aliphatic ether, cyclic ether, poly ether, aromatic ether, and aliphatic ester.
[0023] In the present invention, the step of preparing the precursor solution is characterized by adding one or more of a conductive material and a polymer material to the precursor solution.
[0024] In order to solve the other technical problems mentioned above, the present invention provides a mixed-conductivity azyrodite-based solid electrolyte represented by the following chemical formula 1, characterized by having an electron conductivity of 0.01 to 10,000 mS / cm and an ionic conductivity of 0.1 to 100 mS / cm.
[0025] [Chemical Formula 1]
[0026] (A + ) a (B n+ ) b (X 2- ) x (Y - ) y
[0027] In the above chemical formula 1, A = Li, B = P, X = S, Y = F, Cl, Br, I, and one or more halogen elements, and a + n * b - 2 * x - y = 0, a > 0, x > 0, and at least one of b and y is > 0, while a = 7-y, b = 1, x = 6-y, and 0.1 ≤ y ≤ 2.
[0028] In the present invention, the mixed conductive azirodite-based solid electrolyte is characterized by containing 50 to 100 wt% of an azirodite crystal structure of space group F-43m.
[0029] To solve the above-mentioned other technical problem, the present invention provides an active material-solid electrolyte composite powder characterized by comprising a mixed-conducting azyrodite-based solid electrolyte represented by the following chemical formula 1, having an electron conductivity of 0.01 to 10,000 mS / cm and an ionic conductivity of 0.1 to 100 mS / cm.
[0030] [Chemical Formula 1]
[0031] (A + ) a (B n+ ) b (X 2- ) x (Y - ) y
[0032] In the above chemical formula 1, A = Li, B = P, X = S, Y = F, Cl, Br, I, and one or more halogen elements, and a + n * b - 2 * x - y = 0, a > 0, x > 0, and at least one of b and y is > 0, while a = 7-y, b = 1, x = 6-y, and 0.1 ≤ y ≤ 2.
[0033] To solve the above-mentioned other technical problem, the present invention provides an all-solid-state battery characterized by comprising a mixed-conducting azyrodite-based solid electrolyte represented by the following chemical formula 1, having an electron conductivity of 0.01 to 10,000 mS / cm and an ionic conductivity of 0.1 to 100 mS / cm.
[0034] [Chemical Formula 1]
[0035] (A + ) a (B n+ ) b (X 2- ) x (Y - ) y
[0036] In the above chemical formula 1, A = Li, B = P, X = S, Y = F, Cl, Br, I, and one or more halogen elements, and a + n * b - 2 * x - y = 0, a > 0, x > 0, and at least one of b and y is > 0, while a = 7-y, b = 1, x = 6-y, and 0.1 ≤ y ≤ 2.
[0037] In the present invention, the mixed conductive azirodite-based solid electrolyte is characterized by containing 50 to 100 wt% of an azirodite crystal structure of space group F-43m. Effects of the invention
[0038] According to the present invention, which is a means for solving the above problem, the electronic conductivity and ionic conductivity are controlled according to the degree to which the polar aprotic solvent is carbonized by heat treatment, and in particular, there is an effect of synthesizing a novel azirodite-based solid electrolyte having an ionic conductivity of 0.1 mS / cm or more and an electronic conductivity of 0.01 mS / cm or more.
[0039] In addition, an azirodite-based solid electrolyte raw material comprising a lithium metal-containing material, a transfer catalyst that ionizes lithium metal to transfer ions and electrons, a chalcogen element, and a compound of one or more elements from Groups 2 to 15 and 17 of the periodic table is stirred and reacted in a single solvent, a polar aprotic solvent, so that the reaction between the azirodite-based solid electrolyte raw materials proceeds simultaneously, thereby synthesizing an azirodite-based solid electrolyte precursor in a suspended, dissolved, or combined state thereof, and by merely recovering the powder and heat treating, an azirodite-based, lithium metal ion (Li) with a crystalline or glass-ceramic structure is obtained. + ) It has the effect of easily synthesizing conductive chalcogenide-based solid electrolytes without using expensive and difficult-to-store raw materials such as Li2S.
[0040] In addition, in a lithium metal-containing material that reacts with a compound of one or more elements from groups 2 to 15 and 17 of the periodic table under a polar aprotic solvent, lithium metal alone may be used, and in particular, by preparing a lithium metal-transfer catalyst radical solution formed by reacting lithium metal with a transfer catalyst in a polar aprotic solvent and then reacting it, the time required to dissolve and react the lithium metal can be reduced.
[0041] In addition, the particle size of the suspended precursor can be controlled by physical powder grinding methods such as ultrasonic irradiation, passing through a high-pressure homogenizer, and mechanical grinding during the reaction for preparing the precursor solution, and the particle size of the precursor can be controlled by inducing chemical nucleation and growth of the suspended precursor by controlling the concentration of lithium metal ion-transfer catalyst radicals.
[0042] In addition, after recovering the azirodite-based solid electrolyte precursor powder, the remaining solvent can be recovered and recirculated in a batch or continuous manner for the first process of azirodite-based solid electrolyte synthesis, which not only reduces costs but also has an advantageous effect for mass production. Brief explanation of the drawing
[0043] FIG. 1 is a flowchart showing a method for manufacturing an azirodite-based solid electrolyte according to the present invention. FIG. 2 is an exemplary diagram showing a method for manufacturing an azirodite-based solid electrolyte according to the present invention. Figure 3 is a photograph showing the color change during the synthesis reaction of an azirodite-based solid electrolyte (Li6PS5Cl) according to Example 1. Figure 4 is a graph showing the XRD pattern of an azirodite-based solid electrolyte prepared according to Example 1. Figure 5 is a graph showing the ionic conductivity of an azirodite-based solid electrolyte (Li6PS5Cl) prepared according to Example 1. Figure 6 is a graph showing the measured electron conductivity of an azirodite-based solid electrolyte (Li6PS5Cl) prepared according to Example 1. Specific details for implementing the invention
[0044] The present invention will be described in detail below.
[0045] In one embodiment, the present invention relates to a mixed-conductivity azirodite-based solid electrolyte. Such an azirodite-based solid electrolyte is characterized by having controlled electronic conductivity and ionic conductivity, wherein the electronic conductivity is 0.01 mS / cm or higher and the ionic conductivity is 0.1 mS / cm or higher.
[0046] The azirodite-based solid electrolyte of the present invention is characterized by having a composition represented by Chemical Formula 1.
[0047] [Chemical Formula 1]
[0048] (A + ) a (B n+ ) b (X 2- ) x (Y - ) y
[0049] In Chemical Formula 1 above, A = Li, B = P, X = S, Y = F, Cl, Br, I, and one or more halogen elements. In this case, a + n * b - 2 * x - y = 0, a > 0, x > 0, and at least one of b and y is > 0, wherein a = 7-y, b = 1, x = 6-y, 0.1 ≤ y ≤ 2, and may contain 50 to 100 wt% of the azirodite crystal structure of space group F-43m.
[0050] The azirodite-based solid electrolyte in the present invention comprises A, B, X and Y (A + ) a (B n+ ) b (X 2- ) x(Y - ) y As it is composed of, it is preferable to include lithium metal (A) and chalcogen element (X) instead of the conventional expensive Li2S.
[0051] A stands for lithium (Li) metal.
[0052] B refers to any one or more elements belonging to groups 2 to 15 of the periodic table, and the materials that can be raw materials for B in an azirodite-based solid electrolyte may be one or more selected from the group consisting of B, BX, and BY.
[0053] X represents a chalcogen element such as sulfur (S), selenium (Se), tellurium (Te) of Group 16 of the periodic table and a mixture of these and oxygen (O). In a azirodite-based solid electrolyte, the material that can serve as a source of the chalcogen element may be one or more selected from the group consisting of X and BX, and it is desirable that the oxygen (O) among the chalcogen elements exist only as a mixture.
[0054] Y may include elements such as fluorine (F), chlorine (Cl), bromine (Br), and iodine (I) of Group 17 of the periodic table, and monovalent anions such as CN, OCN, SCN, and N3. For this purpose, the materials that can be raw materials for Y may be one or more selected from the group consisting of AY and BY.
[0055] In addition, as described above, an active material-solid electrolyte composite powder may be formed by including a mixed conductive azyrodite-based solid electrolyte having an electronic conductivity of 0.01 to 10,000 mS / cm and an ionic conductivity of 0.1 to 100 mS / cm.
[0057] In another aspect, the present invention relates to a method for manufacturing a mixed-conductivity azirodite-based solid electrolyte. In this regard, FIG. 1 is a flowchart illustrating a method for manufacturing an azirodite-based solid electrolyte according to the present invention, and FIG. 2 is an illustrative diagram illustrating a method for manufacturing a Li6PS5Cl electrolyte among the azirodite-based solid electrolytes according to the present invention.
[0058] Referring to FIGS. 1 and 2, a method for manufacturing an azirodite-based solid electrolyte according to the present invention comprises the step of manufacturing a precursor solution (S10), the step of recovering a solid electrolyte precursor in powder form (S20), and the step of heat-treating the recovered solid electrolyte precursor powder to manufacture a mixed-conductivity azirodite-based solid electrolyte having controlled ionic conductivity and electron conductivity, with an ionic conductivity of 0.1 mS / cm or more and an electron conductivity of 0.01 mS / cm or more (S30).
[0059] According to the above-described manufacturing method, first, an azyrodite-based solid electrolyte raw material comprising a lithium metal-containing material, a transfer catalyst that ionizes the lithium metal to transfer ions and electrons, a chalcogen element, and a compound of one or more elements from groups 2 to 15 and 17 of the periodic table is reacted in a polar aprotic solvent to produce a precursor solution in which an azyrodite-based solid electrolyte precursor exists in a suspension, dissolution, or a combination thereof through a lithium metal polychalcogenide generated as ions and electrons are transferred from the lithium metal-containing material to the chalcogen element (S10).
[0060] The lithium metal-containing material may be one or more selected from the group consisting of lithium metal, a lithium metal-transfer catalyst radical solution formed by reacting lithium metal with a transfer catalyst in a polar aprotic solvent, and a mixture thereof.
[0061] By using lithium metal alone as a lithium metal-containing material and reacting it simultaneously with a compound of one or more elements from Groups 2 to 15 and Group 17 of the periodic table under a polar aprotic solvent, the lithium metal can dissolve to some extent while dissolving the remaining raw materials. However, in the case of lithium metal, it dissolves quickly in the beginning, but the dissolution rate slows down after a certain point, and it may take a total of about 12 hours to completely dissolve in the polar aprotic solvent, which may not be desirable from a production perspective.
[0062] Accordingly, a lithium metal-transfer catalyst radical solution can be prepared by first reacting lithium metal with a transfer catalyst in a polar aprotic solvent as a lithium metal-containing material, and then reacting it by introducing it into a compound of one or more elements from chalcogen elements, groups 2 to 15 and 17 of the periodic table under a polar aprotic solvent. By using a lithium metal-transfer catalyst solution in which lithium metal is dissolved in advance, the disadvantage of taking approximately 12 hours to completely dissolve in a polar aprotic solvent when using lithium metal alone can be resolved.
[0063] When a reaction is carried out under a polar aprotic solvent, the particle size of the suspended precursor can be physically controlled by powder grinding methods such as ultrasonic irradiation, passing through a high-pressure homogenizer, or mechanical grinding, or the particle size of the precursor can be chemically controlled by inducing nucleation and growth of the suspended precursor by controlling the concentration of lithium metal ion-transfer catalyst radicals, and consequently, the particle size of the azirodite-based solid electrolyte can be controlled.
[0064] In a reaction using lithium metal alone, once the lithium metal dissolves up to 33%, the remaining raw materials can also be dissolved. In other words, as the lithium metal dissolves further, it begins to form particle shapes, and the particle size gradually increases. However, there is a disadvantage in that the size of the initially generated particles grows at a faster rate, causing the size gap between them and other particles generated later to widen. To solve this disadvantage, ultrasonic irradiation, passage through a high-pressure homogenizer, mechanical grinding, or controlling the lithium metal concentration in the lithium metal-transfer catalyst radical solution is attempted.
[0065] When carrying out a reaction in a polar aprotic solvent, the lithium metal-transfer catalyst solution is instantaneously introduced to instantaneously increase the concentration of lithium metal, thereby instantaneously generating nuclei within the solution, which allows for the control of nucleus growth and even particle size control. However, if stirring for the reaction is continued, the particles may continue to enlarge; in this case, the particles can be crushed by applying ultrasound at the time of particle formation, passing through a high-pressure homogenizer, or mechanical grinding, or the number of relatively small particles can be controlled to be higher.
[0066] Preferably, lithium metal alone (e.g., about 33% of the raw material for an azirodite-based solid electrolyte), a chalcogen element, and a compound of one or more elements from Groups 2 to 15 and Group 17 of the periodic table are reacted under a polar aprotic solvent to completely dissolve the lithium metal, and then a lithium metal-transfer catalyst radical solution is instantaneously added to increase the number of seeds and increase the reaction rate. Additionally, ultrasound may be applied to control the reaction so that the seed particles generated during the reaction do not continue to grow larger. However, there is no restriction on the order of addition between the lithium metal alone and the lithium metal-transfer catalyst radical solution.
[0067] In the present invention, "suspension" refers to a suspension in which azirodite-based solid electrolyte precursors in the form of powder or granules are dispersed in a solution without dissolving. In the case of Li6PS5Cl, an example of an azirodite-based solid electrolyte, a solid electrolyte precursor in a suspension state is formed by mixing raw materials of Li, S, P2S5, and LiCl with a transfer catalyst (e.g., naphthalene) under THF. In this case, to ensure that the azirodite-based solid electrolyte precursor is dispersed and formed as an undissolved powder in the solvent, a solvent is contained in a container such as the flask of FIG. 2, and the azirodite-based solid electrolyte raw materials and the transfer catalyst are all placed in the container containing the solvent. A stirring reaction is then performed at room temperature or, in the case of THF, within a range from -108°C to 66°C. That is, the stirring reaction is possible at room temperature, at a temperature between the freezing and melting points of the solvent, and under solvothermic conditions utilizing the vapor pressure of the solvent at high temperature and high pressure.
[0068] The solvent used in the stirring reaction is preferably an ether-based solvent that accelerates the action of the transfer catalyst, and one or more selected from the group consisting of aliphatic mono-ether, aliphatic di-ether, cyclic ether, poly ether, and aromatic ether may be used. In addition, polar aprotic solvents such as aliphatic esters having a reduction potential lower than that of lithium metal may be used.
[0069] Aliphatic monoethers may be one or more of dimethyl ether, diethyl ether, methyl ethyl ether, methyl normal propyl ether, and methyl isopropyl. Aliphatic diethers may be one or more of methylal and glycol dimethyl ether. Examples of cyclic ethers may be one or more of tetrahydrofuran (THF) and tetrahydropyran. Polyethers may be one or more of glycol formal, methyl glycerol formal, dimethylene pentaerythrite, and glycerol mono-formal methyl ether. The aromatic ether may be one or more of anisole, methylanisole, and dimethylanisole. The aliphatic monoester may be one or more of diethyl carbonate, dimethyl carbonate, ethyl methyl carbonate, methyl formate, methyl acetate, ethyl acetate, ethyl propionate, and ethyl butyrate.
[0070] A transfer catalyst is capable of ionizing lithium metal to transfer ions and electrons, and can be described as a material that receives lithium metal ions and electrons from lithium metal and transfers them to chalcogen elements. By using a lithium metal polychalcogenide, which is generated by transferring ions and electrons from a lithium metal-containing material to chalcogen elements through electron transfer, it becomes possible to prepare a precursor solution in which an azyrodite-based solid electrolyte precursor exists in a suspended, dissolved, or combined state.
[0071] That is, by sequentially forming a polychalcogenide of lithium metal ions (e.g., 2Li + S8 → Li2S8 → Li2S6 → Li2S4 → Li2S2 → Li2S) and promoting the reaction with compound B (e.g., P2S5) and compound Y (e.g., LiCl), it is possible to synthesize an azirodite-based solid electrolyte precursor in a solvent in a suspended, dissolved, or combined state.
[0072] This means the transfer catalyst is 2A + 2PAH + X n → 2A + PAH - + X n → A2X n It forms soluble polychalcogenides through the + 2PAH process, acting as an electron donor, and as the electron transfer reaction proceeds, A2X of BX compounds and AY compounds n It can be confirmed that it promotes binding with chalcogenides (e.g., P2S5→ Li2P2S6→ Li4P3S7→ 2Li3PS4) and that ABXY precursors are produced as A is completely dissolved.
[0073] Transfer catalysts that mediate the movement of electrons between lithium metal and chalcogen elements through electron transfer ability can be polycyclic aromatic hydrocarbons (PAHs). Polycyclic aromatic hydrocarbons include naphthalene, acenaphthylene, acenaphthene, diphenyl, fluorene, phenanthrene, anthracene, fluoranthene, pyrene, benzo(a)anthracene, chrysene, benzo(k)fluoranthene, benzo(b)fluoranthene, benzo(a)pyrene, indeno(1,2,3-cd)pyrene, dibenz(a,h)anthracene, and One or more types from the group consisting of benzo(g,h,i)perylene can be selected and used.
[0074] Among them, naphthalene is an aromatic hydrocarbon composed of two benzene rings; because it has a strong carbon-hydrogen bond energy and does not oxidize easily, it possesses the most stable structure among polycyclic aromatic hydrocarbons, making it desirable to use naphthalene as a transfer catalyst.
[0075] Such a precursor solution is a lithium metal polychalcogenide (e.g., Li2S) produced by a transfer catalyst transferring ions and electrons from a lithium metal-containing material to a chalcogen element. n By forming (an integer between 1 and 8), the polychalcogenide is dissolved and dispersed in the solution, and the polychalcogenide is reacted or mixed with element B, element Y, or a compound thereof, so that an azirodite-based solid electrolyte precursor can be formed in a suspended, dissolved, or combined state in the solution.
[0076] Additionally, by adding one or more conductive materials selected from carbon, carbon nanotubes, and graphene to the precursor solution, or a polymer material capable of carbonizing when the powdered solid electrolyte precursor is heat-treated, the degree of carbonization of the polar aprotic solvent can be controlled, and the control of ionic and electronic conductivity can be facilitated.
[0077] Next, an azirodite-based solid electrolyte precursor is recovered in powder form from the precursor solution (S20).
[0078] In the past, to synthesize Li6PS5Cl among argyrodite-based solid electrolytes, 3Li2S + P2S5 → 2Li3PS4 was first synthesized in a suspension state in a polar protic solvent, Li2S and LiCl were dissolved in ethanol, a polar protic solvent, and these solvents were mixed to prepare a dissolved Li6PS5Cl precursor, after which the solvent was evaporated to obtain Li6PS5Cl in powder form. In addition, Li6PS5Cl in powder form could be obtained by reacting in a suspension state in a polar aprotic solvent and evaporating the solvent while some of it was dissolved.
[0079] However, the solvent evaporation process using a rotary evaporator can lead to the coarsening of the powder to be obtained, and the composition may become non-uniform depending on the difference in solubility between salts during the precipitation process. Furthermore, when using a mixed solvent, it is difficult to separate the evaporated polar aprotic solvent from the polar protic solvent, making it difficult to reuse the solvent. If a dispersant is used to prevent powder coarsening, the dispersant with a high boiling point may remain as an impurity on the surface of the azirodite-based solid electrolyte, and the powder obtained in a lumpy state has the disadvantage of requiring a cumbersome process of subsequent heat treatment followed by grinding or sieving.
[0080] On the other hand, the method for manufacturing a precursor in a suspended state according to the present invention allows the azirodite-based solid electrolyte precursor to be dispersed in a solvent in a suspended, dissolved, or combined state, thereby enabling the recovery of only the solid electrolyte precursor powder without separately evaporating the solvent.
[0081] Precursors in a suspended state in solution (e.g., Li6PS5Cl precursor) can be separated and recovered as powdered precursors by one or more methods using natural sedimentation, centrifugation, spraying, filtering, or a hydrocyclone, and precursors existing in a dissolved state or a combined state of suspension and dissolution in solution (e.g., Li7P3S 11 = Li3PS4(suspension) + Li4P2S7(dissolved)) can be separated and recovered as a powder precursor by one or more of heat drying, solvent displacement, and spray drying.
[0082] The azirodite-based solid electrolyte powder obtained by separation and recovery in this way may have a size in the range of 0.1 to 10 µm. If the powder is smaller than 0.1 µm, handling of the powder is not easy, and it is difficult to secure high ionic conductivity due to the interface between powders formed by surfaces with low crystallinity, and if the size exceeds 10 µm, there is the inconvenience of having to perform additional grinding.
[0083] Subsequently, after recovering the azirodite-based solid electrolyte precursor powder from the precursor solution, the remaining solvent can be recovered and reused by reintroducing it into the first process for the synthesis of the azirodite-based solid electrolyte. The solvent separated from the azirodite-based solid electrolyte precursor powder can be recovered and recirculated in a batch manner in a container, or it can be recovered and recirculated in a continuous manner when the azirodite-based solid electrolyte raw material is added at once to synthesize the azirodite-based solid electrolyte precursor simultaneously.
[0084] Finally, a solid electrolyte precursor in powder form is heat-treated to produce an azirodite-based solid electrolyte (S30).
[0085] The process involves heat-treating and crystallizing an azirodite-based solid electrolyte precursor powder recovered from a precursor solution in a suspended, dissolved, or combined state. Since the azirodite-based solid electrolyte precursor powder maintains its size even after undergoing heat treatment, it does not require an additional grinding process.
[0086] Crystallization of the azirodite-based solid electrolyte is achieved through a heat treatment process in which the azirodite-based solid electrolyte precursor powder is heated at 400 to 600°C in one or more atmospheres of vacuum, inert gas, and hydrogen sulfide (H2S) gas.
[0087] When heating, an inert gas environment, a hydrogen sulfide (H2S) gas environment, or vacuum conditions are created so that contact with oxygen or moisture is blocked, and the azirodite-based solid electrolyte powder is heated at 400 to 600°C according to the crystallization characteristics according to the composition. If heat treatment is performed at a temperature below 400°C, the ionic conductivity and electron conductivity of the azirodite-based solid electrolyte do not increase sufficiently, and if heat treatment is performed at a temperature exceeding 600°C, the high ionic conductivity crystal structure of the azirodite-based solid electrolyte may be altered, which is undesirable.
[0088] The azirodite-based solid electrolyte synthesized by this method can increase ionic conductivity and electronic conductivity by causing carbonization of the polar aprotic solvent through heat treatment. That is, for the mixed-conductivity azirodite-based solid electrolyte, a higher value for electronic conductivity is preferable, and it is sufficient if controlled to 0.01 mS / cm or higher, but preferably, it can be controlled to 0.01 to 10,000 mS / cm. However, if the electronic conductivity is excessively high, electron transfer from the current collector to the cathode material is hindered, and it is expected that electrochemical reactions cannot occur, so it can be controlled to 10,000 mS / cm or lower. To increase the electronic conductivity value, a conductive material or a polymer material may be added to the precursor solution during the step of preparing the precursor solution mentioned above. In the case of ionic conductivity, it must be 0.1 mS / cm or higher to enable sufficient lithium ion transfer in the all-solid-state battery, and preferably, it can be controlled to 0.1 to 100 mS / cm.
[0089] As described above, according to the method for manufacturing a mixed-conductivity azirodite-based solid electrolyte of the present invention, an azirodite-based solid electrolyte raw material can be reacted all at once under a polar aprotic solvent through a transfer catalyst to produce an azirodite-based solid electrolyte precursor in a suspended, dissolved, or combined state. After separating and recovering the azirodite-based solid electrolyte precursor powder in the suspended or dissolved state, the azirodite-based solid electrolyte precursor powder can be heat-treated to continuously synthesize an azirodite-based solid electrolyte. In particular, it is significant that a mixed-conductivity azirodite-based solid electrolyte can be synthesized by controlling the ionic conductivity and the electronic conductivity, wherein the ionic conductivity is controlled to 0.1 to 100 mS / cm and the electronic conductivity is controlled to 0.01 to 10,000 mS / cm.
[0091] In another aspect, the present invention relates to an all-solid-state battery comprising an azirodite-based solid electrolyte. Preferably, the all-solid-state battery comprises a positive electrode, a negative electrode, and a solid electrolyte layer disposed between the positive and negative electrodes, wherein the solid electrolytes in the positive and negative electrodes comprise an azirodite-based solid electrolyte prepared by the method described above.
[0092] The positive electrode can be any known material that can be used in an all-solid-state battery and is composed of a positive electrode active material, a solid electrolyte, a conductive material, and a binder. The contact area of the positive electrode active material can be maximized by dry coating it with the above-mentioned mixed-conductivity azirodite-based solid electrolyte. The positive electrode current collector can be stainless steel, aluminum, nickel, titanium, calcined carbon, or aluminum or stainless steel surface-treated with carbon, nickel, titanium, silver, etc., to have high conductivity without causing chemical changes.
[0093] The negative electrode can be a known type, similar to the positive electrode, and may be composed of a negative electrode active material, a solid electrolyte, a conductive material, and a binder, or may be a lithium metal or Li-free negative electrode that does not contain a solid electrolyte. The negative electrode current collector can be applied in various ways as long as it is conductive without causing chemical changes in the all-solid-state battery, and may be copper, stainless steel, aluminum, nickel, titanium, calcined carbon, copper or stainless steel surface treated with carbon, nickel, titanium, silver, etc., or an aluminum-cadmium alloy.
[0094] That is, the all-solid-state battery comprises a positive electrode, a negative electrode, and a solid electrolyte layer, and by including the mixed-conductivity azirodite-based solid electrolyte of the present invention, it is possible to secure physical properties equivalent to or better than those of conventional solid electrolytes.
[0096] The embodiments of the present invention will be described in more detail below. However, the following embodiments are provided merely to aid in understanding the present invention and do not limit the scope of the present invention.
[0097] <Example 1> Azirodite-based solid electrolyte (Li 6 PS 5 Preparation of Cl)
[0098] 0.387 g of lithium (Li) metal, 0.897 g of sulfur (S), 51.242 g of P2S, 0.474 g of LiCl, 0.716 g of naphthalene, and 27.6 ml of tetrahydrofuran (THF) were all placed in a 100 ml flask in a glove box under an argon atmosphere, and stirred with a magnetic bar at room temperature for 14 hours to prepare a precursor solution containing an azyrodite-based solid electrolyte precursor. Subsequently, the precursor solution was centrifuged to recover the powder. The recovered powder was heat-treated at 550°C for 8 hours under an Ar flow environment to prepare a mixed-conductivity azyrodite-based solid electrolyte.
[0099] <Test Example 1> Sediment identification analysis
[0100] In this test example, photographs of the stirring reaction at different time points were analyzed according to Example 1. In this regard, Figure 3 shows the color change during the synthesis reaction of the azirodite-based solid electrolyte (Li6PS5Cl) according to Example 1. Figure 3(a) shows a photograph taken at the time stirring was started in a 100 ml flask containing 0.387 g of lithium metal, 0.897 g of sulfur, 1.242 g of P2S5, 0.474 g of LiCl, 0.716 g of naphthalene, and 27.6 ml of tetrahydrofuran; Figure 3(b) shows a photograph taken 30 minutes after stirring started; Figure 3(c) shows a photograph taken 1 hour after stirring started; Figure 3(d) shows a photograph taken 6 hours after stirring started; and Figure 3(e) shows a photograph taken 14 hours after stirring started.
[0101] Referring to Fig. 3, it can be seen that the initial solution color turned black as polysulfide was formed, and then the reaction with P2S5 proceeded slowly at 1 hour of stirring, and then, as shown in Fig. 3(e), an azirodite-based solid electrolyte precursor in a suspended state was prepared at 14 hours of stirring, after sufficient reaction.
[0102] <Test Example 2> X-ray diffraction analysis
[0103] In this test example, X-ray diffraction spectroscopy (XRD) was performed using the azirodite-based solid electrolyte (Li6PS5Cl) prepared according to Example 1.
[0104] That is, X-ray diffraction analysis was performed on the azirodite-based solid electrolyte prepared in Example 1, and the results are shown in Fig. 4. In this regard, Fig. 4 is a graph showing the XRD pattern of the azirodite-based solid electrolyte prepared according to Example 1.
[0105] Referring to Fig. 4, it can be seen that the azirodite-based solid electrolyte prepared in Example 1, in which a stirring reaction was carried out at room temperature for 14 hours, has diffraction angles (2θ) in the regions of 15.5±0.5°, 18.0±0.5°, 25.5±0.5°, 30.0±0.5°, 31.5±0.5°, 40.0±0.5°, 45.5±0.5°, 48.0±0.5°, 53.0±0.5°, 55.0±0.5°, 56.5±0.5° and 59.5±0.5° as major peaks. These peaks are identical to the peaks of Li6PS5Cl, which has an azirodite-type crystal structure in space group F-43m, and since the peaks caused by impurities are detected to be relatively very low, it can be confirmed that the azirodite-based solid electrolyte prepared in Example 1 is a solid electrolyte having an azirodite-type crystal structure.
[0106] <Test Example 3> Ionic and electronic conductivity analysis
[0107] In this test example, the ionic conductivity was analyzed using an azirodite-based solid electrolyte (Li6PS5Cl) prepared according to Example 1.
[0108] That is, the azirodite-based solid electrolyte prepared in Example 1 was compression molded into a 1 cm diameter mold using 3 tons to produce a molded body having a constant thickness and diameter. Indium was attached to both sides of the manufactured molded body, and a test cell was assembled to measure 1×10⁻⁶ using AC impedance analysis. 6 Ionic conductivity was analyzed by measuring impedance values through a frequency sweep of 0.1 Hz. In this regard, FIG. 5 is a graph showing the ionic conductivity measurement of an azirodite-based solid electrolyte (Li6PS5Cl) prepared according to Example 1.
[0109] In addition, the electronic conductivity was analyzed by applying a voltage of 1V to the above test cell and measuring the current flowing at that time. In this regard, Figure 6 is a graph showing the measurement of the electronic conductivity of an azirodite-based solid electrolyte (Li6PS5Cl) prepared according to Example 1.
[0110] As the ionic conductivity of an azirodite-based solid electrolyte is an important factor in determining the charge / discharge rate and output rate of an all-solid-state battery, as shown in FIGS. 5 and 6, it can be seen that the ionic conductivity of the mixed-conductivity azirodite-based solid electrolyte prepared according to Example 1 of the present invention is controlled to have excellent values of 1.05 mS / cm and the electron conductivity is 0.168 mS / cm.
[0112] In summary, the present invention involves reacting an azirodite-based solid electrolyte raw material comprising a lithium metal-containing material, a transfer catalyst that ionizes lithium metal to transfer ions and electrons, a chalcogen element, and a compound of one or more elements selected from Groups 2 to 15 and Group 17 of the periodic table in a polar aprotic solvent to produce a precursor solution in which an azirodite-based solid electrolyte precursor exists in a suspended, dissolved, or combined state via a lithium metal polychalcogenide generated as ions and electrons are transferred from the lithium metal-containing material to the chalcogen element, and recovering the azirodite-based solid electrolyte precursor in powder form from the precursor solution and then heat-treating it, thereby (A + ) a (B n+ ) b (X 2- ) x (Y - ) y It has the characteristic of being able to synthesize a mixed-conductive azirodite-based solid electrolyte having a composition represented by Chemical Formula 1.
[0113] In particular, the mixed-conductivity azirodite-based solid electrolyte according to the present invention is significant as it is a novel azirodite-based solid electrolyte in which electronic conductivity and ionic conductivity are simultaneously controlled using an organic material such as a polar aprotic solvent.
[0114] As such, the mixed-conductivity azirodite-based solid electrolyte synthesized according to the present invention enables control of ionic conductivity and electronic conductivity, and accordingly, it is expected that the charge / discharge rate and output rate of an all-solid-state battery can be controlled.
[0115] The foregoing description is merely an illustrative explanation of the technical concept of the present invention, and those skilled in the art to which the present invention pertains will be able to make various modifications and variations within the scope of the essential characteristics of the present invention. Accordingly, the embodiments disclosed in the present invention are intended to explain, not to limit, the technical concept of the present invention, and the scope of the technical concept of the present invention is not limited by such embodiments. The scope of protection of the present invention shall be interpreted by the claims, and all technical concepts within an equivalent scope shall be interpreted as being included within the scope of rights of the present invention.
Claims
Claim 1 A step of preparing a precursor solution in which an azirodite-based solid electrolyte precursor exists in a state of suspension, dissolution, or a combination thereof, by means of a lithium metal polychalcogenide generated as ions and electrons are transferred from the lithium metal-containing material to the chalcogen element, by reacting an azirodite-based solid electrolyte raw material comprising a lithium metal-containing material, a transfer catalyst that ionizes the lithium metal to transfer ions and electrons, a chalcogen element, and a compound of one or more elements selected from Groups 2 to 15 and Group 17 of the periodic table in a polar aprotic solvent; and a step of recovering the azirodite-based solid electrolyte precursor in powder form from the precursor solution. A method for manufacturing a mixed-conductivity azirodite-based solid electrolyte, comprising the step of heat-treating the powder-form solid electrolyte precursor to produce an azirodite-based solid electrolyte; wherein the azirodite-based solid electrolyte is characterized in that its electronic conductivity and ionic conductivity are controlled according to the degree to which the polar aprotic solvent is carbonized by the heat treatment. Claim 2 A method for manufacturing a mixed-conductivity azyrodite-based solid electrolyte according to claim 1, wherein the azyrodite-based solid electrolyte is controlled to have an electron conductivity of 0.01 to 10,000 mS / cm and an ionic conductivity of 0.1 to 100 mS / cm. Claim 3 A method for manufacturing a mixed-conducting azyrodite-based solid electrolyte according to claim 1, wherein the azyrodite-based solid electrolyte is represented by the following chemical formula 1 and comprises 50 to 100 wt% of an azyrodite crystal structure of space group F-43m: [Chemical Formula 1](A + ) a (B n+ ) b (X 2- ) x (Y - ) y In the above chemical formula 1, A = Li, B = P, X = S, Y = F, Cl, Br, I, and one or more halogen elements, and a + n * b - 2 * x - y = 0, a > 0, x > 0, and at least one of b and y is > 0, while a = 7-y, b = 1, x = 6-y, and 0.1 ≤ y ≤ 2. Claim 4 A method for manufacturing a mixed-conductivity azirodite-based solid electrolyte according to claim 3, wherein the precursor solution is dissolved and dispersed in the solution by a lithium metal-transfer catalyst radical generated by the reaction between the lithium metal-containing material and the transfer catalyst transferring lithium metal ions and electrons to the chalcogen element to form the lithium metal polychalcogenide, and the polychalcogenide reacts or mixes with the B element, the Y element, or a compound thereof, so that the solid electrolyte precursor is manufactured in a suspended, dissolved, or combined state in the solution. Claim 5 A method for manufacturing a mixed-conductive azirodite-based solid electrolyte, wherein, in claim 1, the heat treatment step is characterized by crystallizing the powder-form solid electrolyte precursor at 400 to 600°C in an atmosphere of one or more of vacuum, inert gas, and hydrogen sulfide (H2S) gas. Claim 6 A method for manufacturing a mixed-conductivity azirodite-based solid electrolyte, wherein, in claim 1, the lithium metal-containing material is selected from the group consisting of lithium metal, a lithium metal-transfer catalyst radical solution formed by reacting the lithium metal with the transfer catalyst in the polar aprotic solvent, and a mixture thereof. Claim 7 A method for manufacturing a mixed-conductive azirodite-based solid electrolyte according to claim 1, wherein the step of recovering the solid electrolyte precursor in powder form is characterized in that the precursor existing in a suspended state in the solution is separated and recovered by one or more methods of filtering, centrifugation, natural sedimentation, spraying, and hydrocyclone, and the precursor existing in a dissolved state or a combined state of suspension and dissolution in the solution is separated and recovered by one or more methods of heat drying, solvent exchange, and spray drying. Claim 8 In claim 1, the transfer catalyst comprises naphthalene, acenaphthylene, acenaphthene, diphenyl, fluorene, phenanthrene, anthracene, fluoranthene, pyrene, benzo(a)anthracene, chrysene, benzo(k)fluoranthene, benzo(b)fluoranthene, benzo(a)pyrene, indeno(1,2,3-cd)pyrene, dibenz(a,h)anthracene, and A method for preparing a mixed-conducting azirodite-based solid electrolyte, characterized by being one or more polycyclic aromatic hydrocarbons (PAHs) selected from the group consisting of benzo(g,h,i)perylene. Claim 9 A method for manufacturing a mixed-conductive azyrodite-based solid electrolyte, wherein, in claim 1, the polar aprotic solvent is one or more selected from the group consisting of aliphatic ether, cyclic ether, poly ether, aromatic ether, and aliphatic ester. Claim 10 A method for manufacturing a mixed conductive azirodite-based solid electrolyte, wherein, in claim 1, the step of manufacturing the precursor solution is characterized by adding one or more of a conductive material and a polymer material to the precursor solution. Claim 11 A mixed-conductive azyrodite-based solid electrolyte represented by the following chemical formula 1, comprising 50 to 100 wt% of an azyrodite crystal structure of space group F-43m, having an electronic conductivity of 0.01 to 10,000 mS / cm and an ionic conductivity of 0.1 to 100 mS / cm, and characterized by being mixed and used in a positive or negative electrode plate of an all-solid-state battery: [Chemical Formula 1](A + ) a (B n+ ) b (X 2- ) x (Y - ) y In the above chemical formula 1, A = Li, B = P, X = S, Y = F, Cl, Br, I, and one or more halogen elements, and a + n * b - 2 * x - y = 0, a > 0, x > 0, and at least one of b and y is > 0, while a = 7-y, b = 1, x = 6-y, and 0.1 ≤ y ≤ 2. Claim 12 delete Claim 13 An active material-solid electrolyte composite powder characterized by comprising a mixed-conductivity azyrodite-based solid electrolyte represented by the following chemical formula 1, containing 50 to 100 wt% of an azyrodite crystal structure of space group F-43m, having an electronic conductivity of 0.01 to 10,000 mS / cm and an ionic conductivity of 0.1 to 100 mS / cm, and being used mixed into a positive or negative electrode plate of an all-solid-state battery: [Chemical Formula 1](A + ) a (B n+ ) b (X 2- ) x (Y - ) y In the above chemical formula 1, A = Li, B = P, X = S, Y = F, Cl, Br, I, and one or more halogen elements, and a + n * b - 2 * x - y = 0, a > 0, x > 0, and at least one of b and y is > 0, while a = 7-y, b = 1, x = 6-y, and 0.1 ≤ y ≤ 2. Claim 14 All-solid-state battery characterized by comprising a mixed-conductivity azyrodite-based solid electrolyte represented by the following chemical formula 1, comprising 50 to 100 wt% of an azyrodite crystal structure of space group F-43m, having an electronic conductivity of 0.01 to 10,000 mS / cm and an ionic conductivity of 0.1 to 100 mS / cm, and being used mixed in the positive or negative electrode plate of an all-solid-state battery: [Chemical Formula 1](A + ) a (B n+ ) b (X 2- ) x (Y - ) y In the above chemical formula 1, A = Li, B = P, X = S, Y = F, Cl, Br, I, and one or more halogen elements, and a + n * b - 2 * x - y = 0, a > 0, x > 0, and at least one of b and y is > 0, while a = 7-y, b = 1, x = 6-y, and 0.1 ≤ y ≤ 2. Claim 15 delete
Citation Information
Patent Citations
sulfide solid electrolyte
KR1020190051962A
A method for manufacturing a sulfide-based solid electrolyte having crystal structure of argyrodite
KR1020190066792A
